Desmatamento, crescimento econômico e desenvolvimento na região Oeste do Pará ao longo das rodovias Transamazônica e Santarém-Cuiabá - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The theme present in this research is about the relationship between the dynamics of deforestation and the economic growth of a certain region of the Brazilian Amazon and what is the impact of this relationship on the development process of this geographical space, against the background of planned population movements for occupation of the region since the building of land transport routes in the 1970s. The main objective of this study is to analyze whether the economic growth that occurred in the region of interest, having as one of its most important bases the deforestation processes, translates into socially distributed development - or qualitative changes for the better in people's lives - in order to have a positive impact on families' quality of life and other aspects of development. There are four general objectives of this study. Analyze broadly how the region became of interest for this study and how the processes of occupation and use of land in its spatial territory took place; What is deforestation and what are its characteristics and importance in the context of the economic growth that has occurred in the region; explain the relationship between economic growth and development in the studied territorial space and analyze the relationship between economic growth and deforestation in the region of interest. To achieve the proposed objectives, the historical deductive methodology was used due to the complexity and constant mutation of the research object. The main results found show that the historical process of economic growth did not translate into full development due to the high degree of inequality present in society from the beginning of the observation until its end. The economy has grown, but in a very concentrated way, causing tensions mainly regarding land tenure and income inequality. It is concluded that the region underwent a new process of conservative modernization, which goes beyond the rural environment and the pact of the ruling elites, to extend to all sectors of society, through the absorption, even by the most disadvantaged social classes, of evolution. productivity of material and immaterial productivity tools, but without changing the fundamental access structures for real social mobility.
Keywords: Amazônia; Desenvolvimento; Desmatamento; Crescimento econômico; CNPQ::CIÊNCIAS AGRÁRIAS; SOCIEDADE, NATUREZA E DESENVOLVIMENTO